REVITALISASI PENDIDIKAN AGAMA ISLAM: DARI TEORITIS MENJADI PRAKTIS - Saefuddin Jazuli (CV. Adiba Aisha Amira, 2024)
Islamic Religious Education (PAI) has role crucial in form character and generational morals young . However , challenges modernization And globalization demand exists update in method PAI teaching to be more relevant And effective . Study This use approach qualitative For understand in a way deep dynamics and revitalization process Islamic religious education from aspect theoretical to practical . use design studies case For analyze implementation approach practical in PAI teaching in several school as the unit of analysis . Through analysis literature And studies cases , articles This explore How integration practice religious in life daily can increase understanding And application Islamic values among student . Results study show that approach practical , involving experience direct , collaborative community , and use technology , capable create more learning​ meaningful And impact . Formulation Problem Study This How design or planning learning theocentric , implementation learning theocentric And evaluation learning theocentric . Results study This is Revitalization Islamic Religious Education with approach theocentric in aspect mark will guide participant educate own ability integrate religious knowledge and knowledge general And own method where a holistic view all entity contain mark divinity .